The Influence Of Price Perception And Service Quality On Customer Satisfaction At PT Telkom Indonesia (Persero) Tbk Regional 1 Sumatra - Allendifa, Auliya; Rini, Endang Sulistya; Fadli, Fadli (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the effect of price perception and service quality on customer satisfaction of PT Telkom Indonesia (Persero) Tbk Regional 1 Sumatra. A quantitative approach was used with a survey method involving 100 active IndiHome customers in Regional 1 Sumatra, selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS 26. The results indicate that price perception has a positive and significant effect on customer satisfaction (t = 4.213; p < 0.05), service quality has a positive and significant effect on customer satisfaction (t = 5.876; p < 0.05), and simultaneously both variables significantly affect customer satisfaction (F = 38.742; p < 0.05) with a coefficient of determination of 44.2%.